Implementasi Media Pembelajaran Mind Map Melalui Metode Problem Based Learning Untuk Meningkatkan Keaktifan Siswa - Kurnia, Fitri; Rahmatullah, Asep (Tarbawi : Jurnal Studi Pendidikan Islami, 2026)
This study describes the implementation of mind map learning media through the Problem-Based Learning (PBL) method to enhance student engagement among grade X students at MA. Sunan Ampel Kepuh Kejayan Pasuruan. Employing a descriptive qualitative approach, the research involved a Fiqh teacher and 25 students as subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The implementation was conducted through five PBL stages integrated with mind mapping. Student engagement increased significantly across multiple dimensions: visual, oral (from 30% to 75%), listening, writing, drawing, mental, and emotional aspects. Supporting factors included teacher competence and adequate infrastructure. Constraining factors encompassed time limitations and diverse student abilities. Positive impacts included deeper conceptual understanding, enhanced critical thinking, improved collaboration, and increased intrinsic motivation. The combination of mind mapping and PBL proved effective in enhancing student engagement comprehensively.